Taat sebelum Hebat: Rahasia Kepemimpinan Kristen yang Bertumbuh dari Ketundukan (International Forum of Researchers and Lecturers, 2025)
Contemporary Christian leadership encounters complex challenges when integrating intellectual, emotional, and spiritual intelligence. Limited understanding of obedience as a leadership foundation results in weakened spiritual development and integrity in ministry. This research employs a qualitative approach through comprehensive literature review, analyzing diverse theological literature, scientific journals, and academic sources discussing Christian leadership and obedience principles. The study reveals the concept of